2019
DOI: 10.33024/jkm.v5i1.888
|View full text |Cite
|
Sign up to set email alerts
|

Faktor- Faktor yang Mempengaruhi Kecemasan Antenatal

Abstract: Antenatal anxiety is one of the factors causing complications in pregnancy, childbirth and infants. It is estimated that more than 20% of pregnant women experience antenatal anxiety, but most cases of antenatal anxiety are not reported because the current antenatal assessment is more focused on physical examination. This research aimed to identify antenatal anxiety and analyzed of factors related to the incidence of antenatal anxiety. This research was a Descriptive with Cross Sectional method. Data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 17 publications
0
1
0
4
Order By: Relevance
“…Indonesia menempati urutan ketiga angka kematian ibu di antara negaranegara ASEAN. Menurut Profil Kesehatan Indonesia.2019, kematian (Hanifah & Utami, 2019).…”
Section: Pendahuluanunclassified
“…Indonesia menempati urutan ketiga angka kematian ibu di antara negaranegara ASEAN. Menurut Profil Kesehatan Indonesia.2019, kematian (Hanifah & Utami, 2019).…”
Section: Pendahuluanunclassified
“…Kelompok usia beresiko merupakan kelompok usia yang secara fisiologi memiliki resiko terjadinya penyulit selama kehamilan dan persalinan. 4 Menurut penelitian (Heriani, 2016) terdapat hubungan yang bermakna antara usia ibu dengan tingkat kecemasan dalam menghadapi masa menjelang persalinan. Hasil analisa hubungan usia ibu yang cemas menghadapi masa menjelang persalinan didapat proporsi responden dengan ibu hamil yang beresiko sebesar 81%, lebih besar dari proporsi responden dengan usia tidak beresiko yang mengalami kecemasan sebesar 29,2%.…”
Section: Hubungan Usia Dengan Kecemasan Ibu Hamilunclassified
“…dengan kecemasan antenatal. 4 Wanita primipara cenderung lebih rentan mengalami kecemasan antenatal dikarenakan belum adanya pengalaman dalam menjalani proses kehamilan dan persalinan. 18 Meskipun terdapat penelitian lain yang menyebutkan multipara lebih rentan mengalami kecemasan antenatal dibandingkan ibu primipara, yang dikarenakan adanya tuntutan dari keluarga terhadap kehamilan saat ini.…”
Section: Oajjhsunclassified
See 1 more Smart Citation
“…Pregnancy-related anxiety is defined as a type of contextual anxiety that includes maternal fears and specific worries about pregnancy, childbirth, maternal and infant well-being, hospital, health professionals, changes in mother's appearance, and mother's future life and role [1]. One study found that out of 144 pregnant women, 26.4% experienced antenatal anxiety [2]. Risk factor for prenatal depression is anxiety in pregnancy and sleep disturbance during pregnancy [3].…”
Section: Introductionmentioning
confidence: 99%